2006
DOI: 10.3892/ijmm.18.5.829
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer T cells ameliorate antibody-induced arthritis in macrophage migration inhibitory factor transgenic mice

Abstract: Abstract. Macrophage migration inhibitory factor (MIF)plays an important role in inflammatory diseases. It has been reported that anti-MIF treatment and mif-gene disruption ameliorate joint inflammation in a mouse model of arthritis induced by anti-type II collagen monoclonal antibodies and lipopolysaccharide (anti-IIC mAb/LPS). In the present study, using the anti-IIC mAb/LPS system, we have analyzed arthritis in MIF-transgenic (MIF Tg ) and wild-type C57BL/6 (WT) mice. We found that MIF Tg mice developed mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…As NKT cells can play diverse roles in different experimental models of disease, i.e. as immune-regulatory [8][9][10][11]34] or -enhancing cells [7,14,15,35], the impact of the HFD on NKT cell functions might differ for individual diseases investigated. Furthermore, when treating patients with certain diseases in which NKT cells are involved in the pathogenesis, it may be important to precisely examine the lipid metabolism prior to therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As NKT cells can play diverse roles in different experimental models of disease, i.e. as immune-regulatory [8][9][10][11]34] or -enhancing cells [7,14,15,35], the impact of the HFD on NKT cell functions might differ for individual diseases investigated. Furthermore, when treating patients with certain diseases in which NKT cells are involved in the pathogenesis, it may be important to precisely examine the lipid metabolism prior to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that NKT cells are involved in various autoimmune, inflammatory and allergic diseases, as well as in the host defence that is induced by the acquired immune system [1,2,[5][6][7]. Successful treatments for autoimmune diseases and metastatic cancers in mice have been achieved by activating NKT cells [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…They did not examine the effects of MIF on cell migration, particularly that of NKT cells. Takagi et al (42) reported that Ab-induced arthritis in MIFtransgenic mice is more aggravating than that in wild-type mice. In their study, a-galactosylceramide may have stimulated NKT cells in spleen to trigger immunomodulation against arthritis by promoting Th2-biased immune deviation.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of MIF, reduced synoviocyte proliferation and increased apoptosis were observed, and this was associated with an increase in synovial p53 expression. Ichiyama et al confirmed that MIF is important in mediating inflammation and joint destruction in collagen-induced arthritis [24], and MIF over-expression in a transgenic model was associated with more severe arthritis [25].…”
Section: Mif Is a Pro-inflammatory Mediator In A Range Of Immune-medimentioning
confidence: 98%